The effectiveness of the Functional Movement Screen at predicting injuries in athletes aged 18-35 years old - Orser, K. S. (Journal of Australian Strength and Conditioning, 2018)
The Functional Movement Screen (FMS) has been shown to be a very reliable screen; however, many practitioners seem to be using it more as a diagnostic tool rather than a screen. There has been some research examining the effectiveness of the FMS in predicting injuries in athletic populations. The purpose of this review was to examine the literature regarding the effectiveness of the FMS in predicting injuries in athletes aged 18-35 years old (ie. Collegiate to professional athletes). The Edith Cowan database was searched using key words. This returned 7 peer-reviewed papers; 4 were published in peer-reviewed journals and 3 were thesis papers for a Master`s or PhD. All found the FMS to have high inter- (experienced = > 0.8 kappa value and novice = 0.6-0.79 and > 0.8 kappa value) and intra- (experienced, R = 0.946 and moderate experience, R = 0.771) rater reliability. Some found significance at a total score of = 14. They saw increased risk of injury (ROI) below this total score. 2 papers found an upper limit where athletes above that score saw increased ROI. This suggested a possible "optimal range" score. It also suggested a potential connection to movement variability based on the athletic populations being tested (cyclical sport athletes vs multi-planar sport athletes). More research needs to be done in this area as current research is sparse and inconclusive. In conclusion, practitioners and coaches, if they choose to use the FMS, they should remember this is not a diagnostic test, but rather a screen. If an athlete scores within a range 15-17, the athlete can continue to performance testing. If an athlete scores = 14 or = 18 then further testing by a physiotherapist should be done before moving forward with performance testing.